In sight and in order : racial legibility, racializing surveillance, and Singapore's Malay problem, 1980-1990 - Muhammad Hydar Saharudin (Nanyang Technological University, 2022)
To the extent that surveillance has implemented distinct notions of life and rule, it has been conditioned by particular social, political, and material categories. Race has been one such determinant, and its resulting differentials have been especially applicable to Singapore’s indigenous Malay minority. Since the colonial age, the Malays of Singapore have struggled against their persistent marginality. In official and mainstream discourses, this peripheral state has been explained by fictions of Malay deviance, deficiency, and duplicity. This materiality and narrative has been popularly known as the “Malay problem”.